The Hegemony of English - Macedo, Donaldo; Dendrinos, Bessie; Gounari, Panayota (Series in Critical Narrative, 2003)
'[P]erhaps the best analysis of the English-only movement in the US and the ramifications worldwide of language policies favouring English ...It displays a dazzling grasp of the many meanings of language and the politics that underlie language policy and educational discourse.' Stanley Aronowitz, City University of New York 'In the present political climate, racism and classism often hide behind seemingly technical issues about English in the modern world. The Hegemony of English courageously unmasks these deceptions and points the way to a more humane and sane way to discuss language in our global world.' James Paul Gee, University of Wisconsin, Madison The Hegemony of English succinctly exposes how the neoliberal ideology of globalization promotes dominating language policies. In the United States and Europe these policies lead to linguistic and cultural discrimination while, worldwide, they aim to stamp out a greater use and participation of national and subordinate languages in world commerce and in international organizations such as the European Union. Democracy calls for broad, multi-ethnic participation, and the authors point us toward more effective approaches in an increasingly interconnected world.